2015
DOI: 10.1080/07317115.2015.1120257
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training Program to Improve Working Memory in Older Adults with MCI

Abstract: Results suggest that WM was enhanced in both groups of older adults with MCI. Cogmed was better on one core WM measure and had higher ratings of satisfaction. The Sham condition declined on adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 82 publications
5
90
0
1
Order By: Relevance
“…Five clinical studies were randomized controlled clinical trials (McAvinue et al, 2013; Corbett et al, 2015; Rose et al, 2015; Walton et al, 2015; Hyer et al, 2016), and one study included two randomly allotted intervention groups (Bozoki et al, 2013). All of them applied only computerized cognitive training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five clinical studies were randomized controlled clinical trials (McAvinue et al, 2013; Corbett et al, 2015; Rose et al, 2015; Walton et al, 2015; Hyer et al, 2016), and one study included two randomly allotted intervention groups (Bozoki et al, 2013). All of them applied only computerized cognitive training.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the studies in Table 1 indicate that computerized cognitive training can lead to the improvement of cognitive functions such as reasoning skills (Corbett et al, 2015), short-term memory (McAvinue et al, 2013), working memory (Hyer et al, 2016), processing speed and visual working memory (Walton et al, 2015) in particular. However, this training should be performed over a longer time span since a short-term cognitive training mainly has an impact on short-term memory with temporary effects (McAvinue et al, 2013; Walton et al, 2015).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…We found 19 studies in which 11 digital cognitive training programs for older people with cognitive impairment and dementia were mentioned. The selected papers consisted of ten RCTs (Gaitán et al, 2012;Zaccarelli et al, 2013;Fiatarone Singh et al, 2014;Barban et al, 2015;Cavallo et al, 2016;Hyer et al, 2016;Suo et al, 2016;Bahar-Fuchs et al, 2017;Hagovská et al, 2017;Cavallo and Angilletta, 2018), five pre-post studies (Gigler et al, 2013;González-Palau et al, 2014;Hwang et al, 2015;Vermeij et al, 2017;Mendoza Laiz et al, 2018), two studies with repeated measures design (Eckroth-Bucher and Siberski, 2009;Vermeij et al, 2016), one pilot study (Danassi, 2015), and one study protocol for an RCT (Vanova et al, 2018).…”
Section: Characteristics Of Computerized Programsmentioning
confidence: 99%
“…The results showed that people with mild and moderate impairment receiving a combination of stimulation techniques enhanced the logical memory domain and that these improvements remained 8 weeks after the intervention. Three studies were identified regarding the use of the computer-based cognitive training program Cogmed (Hyer et al, 2016;Vermeij et al, 2016Vermeij et al, , 2017. Hyer et al (2016) conducted an RCT that examined the effectiveness of Cogmed in older adults with MCI.…”
Section: Cognitive Stimulation Programmentioning
confidence: 99%
“…What sorts of interventions work-and on what outcomes-for individuals with cognitive conditions? Hyer and colleagues describe a RCT of computerized cognitive training plus in-person coaching for improving working memory in individuals with MCI (Hyer, Scott, Atkinson, Mullen, Lee, Johnson, & McKenzie, 2016) present. Those in the intervention group (n = 35) improved relative to a sham group (n = 35) on some measures in group x time analyses; on other measures the sham group improved equally.…”
Section: Fellow Clinical Gerontologistsmentioning
confidence: 99%